Law and the utopian imagination - Sarat, Austin; Douglas, Lawrence; Umphrey, Martha Merrill (Amherst series in law, jurisprudence, and social thought., 2014)
This is a project of exploration and resuscitation of idea of utopianism within legal discourse. Instead of mapping out the contours of a familiar terrain, the contributors seek to explore the possibilities of a productive engagement between the utopian and the legal imagination.